PROGRAMAS CORPORATIVOS DE DESENVOLVIMENTO DA CAPACIDADE DE AUTO-SUSTENTO DE COMUNIDADES: AVALIAÇÕES E CONSIDERAÇÕES À LUZ DE UM ESTUDO DE CASO - Ferreira, Moacir Porto (2005)
Known as the fourth wave of the modern management, the Corporative Social Responsibility - CSR - possess diverse forms of application and results. The worldwide companies have bet in the corporative social responsibility as element of conquest of competitive advantage, through diverse involving actions of stakeholders - between them the community. Specifically in activities where the communities have its economy widely dependent of the plants manufacter, one becomes necessary to understand and to promote the diversity economic and to reduce the relation of dependence, lined up to the sustainable development. This text analyzes one of the programs of auto-development of communities, being based on a study of case of a project of strategical planning, sponsored for a private company. Through it, elements of analysis of the Corporative Social Responsibility search, evaluating the intersection of this with the case study and studied project